Does thermodynamics have a hamiltonian? - Thun, Winter Chee Siong. (2009)
Thermofluid, it is one of the most complicated dynamic systems known to the mankind since before the “time” was first created. In fact, all the real fluids existing in our universe are thermofluid in their very own nature. Thus we have no choice but trying to understand it as much as we could with any mean we could access to. As Hamiltonian is known for best for its simplicity and adaptability in our classical mechanics, hence this project was founded with the aim to search for the Hamiltonian of the thermodynamic system.